New Balintawak Market reconfiguring the city market in changing times - Ong, Kayla Meagan Y. (College of Architecture, University of the Philippines Diliman, 2020)
As time passes, more and more of the world's population are moving to urban areas. As a result, urbanization has taken its toll on the supply and demand of city resources. City land has become scarce, with increasing land values over the years. Moreover, advancements in technology and mobility have brought rapid changes in urban lifestyles, which in turn have implications on the way people use physical space in the city. Thus, to lessen further strain on city resources and to adapt to rapid change, there must then be a reimagination and a stronger rationalization of the day urban spaces are designed. City markets have long been an integral part of the urban landscape. It serves as an affordable source of fresh produce in the city, an avenue for social exchange, and a public institution open to people from all walks of life. However, while the urban landscape grew and developed over the years, city markets have remained untouched; some even in disrepair and decay. With this, there lies an opportunity to mitigate both issues simultaneously through a purposeful redevelopment of the city market. This project aims to rethink how markets can be reconfigured to address both current needs and future trends in exploring a more vertical and flexible development. Research methods include site observations, interviews, and literature review. The result is a typology that offers different flows of movement in a vertical development, reorganizes activity flows in the market, and allows for the integration of non-market functions on site in an exploration into how the urban market can adapt to changing times.